Filozofija športa kot most med prakso in teorijo športa - Jošt, Bojan (Šport (Ljubljana), 2018)
Sports philosophy as the love of wisdom and tendency to encourage rational activities in the life of the modern civilisation has also become important in the discussion of sports culture from both practical and theoretical aspects. Sports philosophy is not striving to precisely define its role and mission, but mostly tries to be useful in endeavours towards quality development of the culture of sport. The basic purpose of sports philosophy is to pose questions and seek answers about those substantive issues that are topical for society and individuals and that help improve the quality of sports activities and satisfaction of stakeholders. Sports philosophy studies its subject without any assumptions, because these are constantly appearing and changing. Its method and subject are not rigorously predefined, as they are redefined anew every time. The philosophical process in which people seek clarity about themselves and their world cannot be completed and it represents an original task for any era. People are rational beings and they decide for themselves freely. However, a creature so determined needs constant rational reflection on the foundations of their essence and their acts. Philosophical questions concern any person; philosophising is a source activity that is innate to a self-responsible human soul. The first philosophical question 'What is sport?' belongs to the basic ontological questions of sports philosophy, drawing behind many other questions that need to be answered from different philosophical aspects (ontology-metaphysics, teleology, axiology, anthropology, ethics, aesthetics, logics, gnoseology-epistemology, pragmatics, terminology, history and others). The vertical and horizontal divisions are not that important for the development of sports philosophy, it is much more important that it is successful and beneficial in the search for answers to topical questions and solving of the problems in sports practice, science and theory. Sports philosophy has been gaining ground as a bridge between practice and sports theory. Sport has become an indispensible part of life in the contemporary civilisation and characteristically co-creates its culture which is increasingly intertwined with the achievements of modern science and technology, the foundations of which rest on philosophy. However, sports philosophy is not and cannot be only a cognitive science. It is also a spiritual realm that gives meaning to practice and science as well as inspires hope, fairness, beauty, humanity and many other values of modern life, also contributing to the creative lifestyle of the modern civilisation in the development of sports culture.
Keywords: filozofija športa; praksa; šport; teorija